2014
DOI: 10.1007/s00464-014-3628-1
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic and physiologic outcomes one year after peroral esophageal myotomy (POEM) for treatment of achalasia

Abstract: In this series, POEM resulted in greater than 90% symptomatic treatment success at mean 15-month follow-up. Rates of iatrogenic gastroesophageal reflux, as measured both by symptoms and 24-h pH monitoring, appeared to be on par with recent studies of patients undergoing laparoscopic Heller myotomy and pneumatic dilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
63
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(70 citation statements)
references
References 22 publications
5
63
1
1
Order By: Relevance
“…There have been a few reports of recovery of esophageal body peristalsis after POEM for achalasia. Forty-seven percent of patients had partial recovery of peristalsis in an early European multicenter series of POEM, 19 and 36% of achalasia patients in another single-center study showed some return of normal peristalsis (≥ 70% peristalsis) on post-operative HRM.…”
Section: Short-term Outcomesmentioning
confidence: 91%
See 1 more Smart Citation
“…There have been a few reports of recovery of esophageal body peristalsis after POEM for achalasia. Forty-seven percent of patients had partial recovery of peristalsis in an early European multicenter series of POEM, 19 and 36% of achalasia patients in another single-center study showed some return of normal peristalsis (≥ 70% peristalsis) on post-operative HRM.…”
Section: Short-term Outcomesmentioning
confidence: 91%
“…POEM has also demonstrated a significant reduction of TBE column height, LES pressure, and integrated relaxation pressure in most cases. 19,26,32 EndoFLIP provides a quantitative assessment of luminal patency and sphincter distension, and recently has been increasingly reported as a method of assessing the adequacy of myotomy. EGJ distensibility measurements on EndoFLIP have been shown to correlate better with postoperative symptoms compared to manometric pressure measurements.…”
Section: Short-term Outcomesmentioning
confidence: 99%
“…Accordingly, the reduction in the LES pressures was 22.8 mmHg ( Table 1). Several studies also reported objective improvement in esophageal emptying on barium esophagram (38,43,44). However, it should be recognized that the median follow up for most studies remains short and it will be important to follow and understanding whether POEM will be durable in the longer term.…”
Section: Single Arm Studiesmentioning
confidence: 99%
“…In a study of patients who underwent POEM, post-treatment outcomes, including symptoms and LES relaxation pressure, were improved after a mean of 15 months follow-up. Among 41 patients, 47% of those with completely absent preoperative peristalsis exhibited partial recovery of peristalsis (5).…”
Section: Introductionmentioning
confidence: 99%
“…Partial recovery of peristalsis has been reported in some patients with achalasia after endoscopic intervention, including POEM; however, the exact mechanism of this phenomenon remains unclear (5)(6)(7)(8)(9). We conducted the present study to investigate the recovery of peristalsis of the esophageal body and to evaluate the pressure changes on manometry before and after endoscopic intervention in patients with achalasia.…”
Section: Introductionmentioning
confidence: 99%